RELEVANSI MATA KULIAH BERKARYA (MKB) KONSENTRASI MESIN OTOMOTIF PADA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SEBELAS MARET SURAKARTA DENGAN KEBUTUHAN INDUSTRI JASA OTOMOTIF DAN SEKOLAH MENENGAH KEJURUAN - Ramdani, Sulaeman Deni (Jurnal Nosel, 2012)
The objective of this research is to find out the relevance of practical subjects (MKB-Mata Kuliah Berkarya) concentrated on automotive engine in Educational Study Program in Sebelas Maret University of Surakarta with industrial need of automotive services and vocational high school. This research includes evaluation research using descriptive method with qualitative and quantitative approaches. Conclusion of this research is, the appropriate level between MKB concentrated on automotive engineering of PTM JPTK FKIP UNS with industrial need of automotive services is stated ?very appropriate/ very high? (81,27 % is appropriate and 18,73 % is not appropriate), and the appropriate level between MKB concentrated on automotive automotive engineering of PTM JPTK FKIP UNS with Vocational High School  is stated ?very appropriate/ very high? (83,34 % is appropriate and 15,66 % is not appropriate).